2021
DOI: 10.1001/jamasurg.2021.0884
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intravenous Tranexamic Acid With Thromboembolic Events and Mortality

Abstract: IMPORTANCE Tranexamic acid (TXA) is an efficient antifibrinolytic agent; however, concerns remain about the potential adverse effects, particularly vascular occlusive events, that may be associated with its use.OBJECTIVE To examine the association between intravenous TXA and total thromboembolic events (TEs) and mortality in patients of all ages and of any medical disciplines.DATA SOURCE Cochrane Central Register of Controlled Trials and MEDLINE were searched for eligible studies investigating intravenous TXA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
2
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 195 publications
(129 citation statements)
references
References 246 publications
3
107
2
5
Order By: Relevance
“…Data from 216 trials have shown that the drug does not significantly increase thromboembolic events (RR 1.02; 95% CI 0.94 to 1.11) even in patients with a history of thromboembolism. 93 In conclusion, TXA appears to be a safe drug that does not confer a significant additional risk of thromboembolism. Clinicians can consider its use for concomitant TBI in the setting of polytrauma given its proven mortality benefits on extracranial bleeding and possible benefit on TBI until further high-quality research is published.…”
Section: Circulation: Is Tranexamic Acid the Solution We Need?mentioning
confidence: 87%
“…Data from 216 trials have shown that the drug does not significantly increase thromboembolic events (RR 1.02; 95% CI 0.94 to 1.11) even in patients with a history of thromboembolism. 93 In conclusion, TXA appears to be a safe drug that does not confer a significant additional risk of thromboembolism. Clinicians can consider its use for concomitant TBI in the setting of polytrauma given its proven mortality benefits on extracranial bleeding and possible benefit on TBI until further high-quality research is published.…”
Section: Circulation: Is Tranexamic Acid the Solution We Need?mentioning
confidence: 87%
“…Recent meta-analysis of 216 studies including 125 550 patients demonstrated no increase in VTE or myocardial infarction or cerebral infarction events over patients who did not receive TXA. 7 Another recent paper showed no increase in MI or VTE events in approximately 26 000 patients with history of coronary artery disease undergoing elective hip and knee arthroplasty procedures. 8 TXA appears to be a safe medication in terms of causing blood clots or other coagulation complications.…”
Section: Discussionmentioning
confidence: 97%
“…The prevalence of bleeding due to anticoagulation was low in our analysis but point of care technology provides information on coagulation dysfunction and the use of anticoagulation, including NOACs. The use of an anti brinolytic is safe and recommended [32]. Blood sample collections should be reduced to the absolute necessary numbers, blood sample collection tubes should draw as little blood volume as possible, and return systems for blood sample collections should be established.…”
Section: Discussionmentioning
confidence: 99%